Purpose in Mufasa’s Resilience in Mufasa: The Lion King (2024) - Dwi Ainur Riza; Rommel Utungga Pasopati; Kusuma Wijaya (PT. Padang Tekno Corp, 2026)
This article examines the role of purpose in shaping Mufasa’s resilience in Barry Jenkins’s film Mufasa: The Lion King (2024). Derived from an undergraduate thesis, this study focuses on purpose as one of the main reasons behind resilience based on Edith Grotberg’s resilience theory. Using a qualitative descriptive method, the data are taken from Mufasa’s dialogues, actions, and narrative contexts presented in the film. The findings reveal that Mufasa’s strong sense of purpose particularly his commitment to protecting others, maintaining justice, and upholding the Circle of Life functions as a central psychological force that motivates him to endure hardship, loss, and adversity. Purpose enables Mufasa not only to survive difficult circumstances but also to transform suffering into moral strength and leadership capacity. This study concludes that purpose is a foundational element of Mufasa’s resilience.